Pendampingan Integrasi Metode Pembelajaran Tradisional dan Modern pada Pembelajaran Kitab Safinatun Naja di Pondok Pesantren Nurul Qur’an Ponorogo - Beni Miftahul Huda; Muhamad Asvin Abdur Rohman (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This community service article analyzes the integration of traditional and modern methods in teaching Safinatun Naja at Nurul Qur’an Islamic Boarding School, Ponorogo, using the ABCD approach. The study was motivated by students’ boredom with one-way traditional methods. Through four stages—discover, dream, design, and destiny—data were collected via observation, interviews, and documentation, then analyzed qualitatively. The results show that asset-based integration strengthens traditional methods (bandongan, sorogan, memorization, tiqror) while combining them with modern approaches (collaborative and experiential learning), leading to greater student participation, focus, comprehension, and interaction. This approach is effective, participatory, and offers a sustainable model for Islamic education development.